Morbidity Pattern in Psychiatry Ward in a Tertiary Care Hospital - Rai, Neena; Sharma, Puspa Prasad; Chettri, Elina; Karmacharya, Swikriti; Rijal, Dinesh (Journal of Psychiatrists’ Association of Nepal, 2023)
Background: Worldwide mental health conditions are in increasing trend. South Asian countries report the highest prevalence of common mental disorders globally, which accounts for 8.8% to 16.6% of the total burden of disease. In Nepal, the prevalence of mental disorders among adults and children is 13.2% and 11.2%, respectively. In Nepal, there is limited data on the pattern of morbidity in inpatient psychiatric wards. Hence, the need is felt to carry out this study to monitor the psychiatric morbidity patterns of patients admitted to the psychiatric ward. Methods: This is a retrospective, cross- sectional study conducted in Kist Medical College. After ethical approval from Institutional Review committee, the data of all patients admitted to Psychiatry Ward of Kist Medical College Teaching Hospital from 14 th April, 2022 to 13 th April, 2023 were collected from Record section. We used ICD-10 and CDDG criteria for the diagnosis of mental and behavioral disorders. Data was analyzed using SPSS version 16. Results: Out of 285 patients 70.40% patients belonged to age group 25-54 years .The mean age with standard deviation was 55.4±72.3 years. Most of the patients were Male (72.60%) and Janajati (44.80%). The most common diagnosis was Alcohol Dependence Syndrome. The duration of hospital stay of most (46.90%) of the patient was 1-2 weeks. Conclusion: The most common diagnosis for which admission was made in Kist Medical College was Alcohol Dependence Syndrome. This indicate that the alcohol related disorder may have important implications for care and planning in the community. The overall outcome was satisfactory.